AJARAN AGAMA HINDU DALAM TEKS TATWADJNYANA - I Wayan Sudiarta (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2019)
Hinduism is a strong foundation and acts as a guide and benchmark in every step of human life towards maturity that is in line with values, norms, customs and culture based on dharma, in order to achieve happiness both physically and mentally. The teachings of Hinduism really need to be instilled in today's modern era which is full of moral degeneration. Times may develop, but must continue to uphold local wisdom. Local wisdom refers to Balinese literature that animates the nuances of longing adopted or packaged into an art both in the form of poetry and prose. Classic works in the form of poetry, for example: kekawin, palawakya, kidung, gaguritan, and in the form of prose such as: satua, tutur, text, parwa, and text. As is known from the point of view of Hinduism as a whole many literary works that support it are in various forms of written work (literature). As is known, traditional Balinese classical works have begun to fade in the midst of society along with the times. In this case a media or means is needed which is capable of realizing this, namely through treatments in the form of literary works in the form of text, namely the Text of the Tatwadjnyana. Tatwadjnyana text is a classic literature that stores various teachings of Hinduism which are indeed very necessary to be developed and more intensive research and study efforts are held, so that all contents can be understood, understood, and applied to Hindus especially about the Teachings of Religion of Religion.Keywords: Teachings of Hinduism and Text of Tatwadjnyana